Materiali per una sociologia dell’amicizia - Bettin Lattes, Gianfranco (SocietàMutamentoPolitica, 2023)
The excessive individualisation that characterises our age deprives and deforms social relations, and gives rise to painful loneliness and other forms of malaise. The sociological study of friendship, which is unfortunately still underdeveloped, makes it possible to analyse in depth the complexity of contemporary subjectivity and the problems it faces. This essay revisits the contributions of a classical author, Georg Simmel, and two contemporary authors, Birgitta Nedelmann and Francesco Alberoni. The interweaving of their analyses, based on different methodologies, shows how friendship remains a fundamental and indispensable resource for human existence, even in so-called modernity. The analytical elements described here are intended to stimulate further studies towards a more systematic sociology of friendship.